Telemedicine in the Digital Era: Changing the Face of Health Services with Virtual Technology - Sulasmi Anggo; Wahyudin Rahman; Som Chai; Chai Pao (Yayasan Adra Karima Hubbi, 2025)
The rapid advancement of digital technology has transformed healthcare delivery, with telemedicine emerging as a vital tool for improving accessibility, efficiency, and patient-centered care. The COVID-19 pandemic accelerated the adoption of telemedicine, highlighting its role in bridging geographical barriers and optimizing medical consultations through virtual platforms. Despite its benefits, challenges such as regulatory issues, technological disparities, and concerns about patient data security remain significant obstacles to its widespread implementation. This study aims to examine the impact of telemedicine on modern healthcare services, evaluate its effectiveness in improving patient outcomes, and identify barriers to adoption. A systematic review approach was used, analyzing peer-reviewed studies, clinical reports, and policy papers published between 2018 and 2024. The findings indicate that telemedicine enhances healthcare accessibility, reduces consultation wait times, and lowers healthcare costs, particularly in remote and underserved areas. However, limitations such as uneven internet infrastructure, resistance from healthcare providers, and variations in legal frameworks hinder its optimal utilization. This study concludes that telemedicine represents the future of digital healthcare, requiring further technological advancements, regulatory standardization, and healthcare professional training to maximize its potential. Future research should explore AI-integrated telemedicine models and their role in improving diagnosis and treatment personalization.